Living alone is associated with a higher prevalence of psychiatric morbidity in a population-based cross-sectional study - Chen, Te-Yu; Geng, Jiun-Hung; Chen, Szu-Chia; Lee, Jia-In (Frontiers in Public Health, 2022)
Background Living alone has been linked to poor mental health, however large-scale epidemiological studies on the association between living alone and psychiatric morbidity including depression and anxiety are lacking. The aim of this study was to investigate this issue in a large Taiwanese cohort. Methods In this cross-sectional study, we enrolled 121,601 volunteers from 29 community recruitment stations in Taiwan and divided them into two groups based on whether or not they lived alone. Psychiatric morbidity was defined as a Generalized Anxiety Disorder 2-item score ≥ 3, Patient Health Questionnaire 2-item score ≥ 3, or self-reported depression. Logistic regression was used to explore the associations between living alone and psychiatric morbidity. Results The participants who lived alone had a higher prevalence of psychiatric morbidity [odds ratio (OR) = 1.608, 95% confidence interval (CI) = 1.473 to 1.755] after adjusting for potential confounders. In a subgroup analysis, married subjects who lived alone and divorce/separation (OR = 2.013, 95% CI = 1.763 to 2.299) or widowing (OR = 1.750, 95% CI = 1.373 to 2.229) were more likely to have psychiatric morbidity than those who were married and not living alone. Conclusions Our findings suggest that living alone is a risk factor for psychiatric morbidity, especially for married subjects who live alone in concordance with divorce, separation, or the death of a spouse.